Analysis of Energy Input–Output of Farms and Assessment of Greenhouse Gas Emissions: A Case Study of Cotton Growers - Abbas, Adnan; Zhao, Chengyi; Waseem, Muhammad; Ahmed khan, Khurshied; Ahmad, Riaz (Frontiers in Environmental Science, 2022)
The concept of agricultural and environmental sustainability refers to minimizing the degradation of natural resources while increasing crop productions, assessment of inflow and outflow energy resources is helpful in highlighting the resilience of the system and maintaining its productivity. In this regard, the current study evaluated the amount energy input-output of cotton productions and their environmental interventions. Data is randomly collected from 400 cotton farmers through face-to-face interview. Results suggested that the major energy is consumed by three culprits i.e., chemical fertilizer, diesel fuel, and irrigation water (11532.60, 11121.54, and 4531.97 MJ ha-1, respectively). Total greenhouse gas (GHG) emission is 1106.12 kg CO2eq ha-1 with main share comes from diesel fuel, machinery and irrigation water. Stimulating data of energies e.g., energy use efficiency (1.53), specific energy (7.69 MJ Kg-1), energy productivity (0.13 kg MJ-1) and net energy gained (16409.77 MJ ha-1). Further analysis using data envelopment analysis (DEA), submitted that low technical efficiency i.e., 69.02% is the most probable cause of poor energy use efficiency. The impermanent trend in growth of energy efficiency has been witnessed with plausible potential of energy savings from 4048.012 to 16194.77 MJ ha-1 and a reduction of 148.96 to 595.96 kg CO2eq ha-1 in GHG emission. Cobb-Douglas production function is further applied to discover the associations of energy input to output, which inferred that chemical fertilizer, diesel fuel, machinery and biocides have significant effect on cotton yield. The MPP values obliged that the additional use in energy (1MJ) from fuel (diesel), biocides and machinery can enhance cotton yield at the rate of 0.35, 1.52 and 0.45 kg ha-1, respectively. Energy savage best links with energy sharing data i.e., 55.66% (direct), 44.34% (indirect), 21.05% (renewable), and 78.95% (nonrenewable) further unveiled the high usage of nonrenewable energy resources (fossil fuels) that ultimately contributes to high emissions of GHGs. We hope that these finding could help in management of energy budget that we believe will reduce the high emissions of GHGs.